Analysis and Design of Control Systems Using Matlab - Dukkipati, R.V. ([S.l.] : New Age Science, 2009)
KEY FEATURES: -Step by step explanations guide through the complex material involving a diverse variety of concepts. -Proper allocation and extensive use and application of MATLAB. -Detailed illustrations of solution methods save a lot of time and effort in understanding problems and theoretical concepts. ABOUT THE BOOK: The book Analysis and Design of Control Systems using MATLAB, is designed as a supplement to an introductory course in feedback control systems for undergraduate or graduate engineering students of all disciplines. Feedback control systems engineering is a multidisciplinary subject and presents a control engineering methodology based on mathematical fundamentals and stresses physical system modeling. This book includes the coverage of classical methods of control systems engineering: introduction to control systems, matrix analysis, Laplace transforms, mathematical modeling of dynamic systems, control system representation, performance and stability of feedback systems, analysis and design of feedback control systems, state space analysis and design, MATLAB basics and MATLAB tutorial. The numerous worked examples offer detailed explanations, and guide the students through each set of problems to enable them to save a great deal of time and effort in arriving at an understanding of problems in this subject. Extensive references to guide the students to further sources of information on control systems and MATLAB is provided. In addition to students, practising engineers will also find this book immensely useful. Also available: Compressible Flow - ISBN 1906574324 MATLAB for Mechanical Engineers - ISBN 1906574138.
Keywords: Control Systems; Matlab